Effect of insecticides on the secondary spread of tomato severe rugose virus (ToSRV) and tomato chlorosis virus (ToCV) by Bemisia tabaci MEAM1, spread distance of ToSRV, and a nanotechnology approach to chemical management of the vector - Oliveira, Felipe Franco de (2024)
Tomato is considered one of the leading agricultural products in Brazil and the world. However, several factors can affect tomato crops, such as diseases caused by the tomato severe rugose virus (ToSRV) and tomato chlorosis virus (ToCV). Both viruses are transmitted by Bemisia tabaci Middle East-Asia Minor 1 (MEAM1). Epidemiological studies have shown that the arrival of the inoculum and the development of the ToSRV and ToCVepidemics in tomato fields occurs mainly through primary infections with the influx of viruliferous vector, which makes external sources of inoculum important in both virus epidemics. However, the hypothesis that the inoculum that causes epidemic development might be related near the tomato crop has yet to be explored. For that, the first objective was to evaluate the short-range flight (10, 20, 30, and 50 meters) of B. tabaci MEAM1, using mark-release-recapture insects, and consequently, the transmission of ToSRV to tomato plants placed at increasing distances from a release point. The efficacy of two protein sources (pasteurized chicken egg-white albumin and commercial soy-based extracts as sources of albumin and lecithin) and two dyes (blue or pink) used as insect markers was also evaluated. The whiteflies reached a maximum of 30 m from the release point, and no ToSRV-infected tomato plants were detected at 50 m. The proteins or the dyes did not affect B. tabaci MEAM1 mortality, although field tests showed that fewer marked than unmarked insects were recaptured. These findings reinforce the suspicion that the epidemic-supporting source of the ToSRV inoculum must be close to the tomato crop. The second objective studied the hypothesis that, as inoculum sources strong enough to sustain high incidences by primary dissemination alone are unlikely, secondary dissemination might occur, even with efficient vector control. The incidence of ToSRV and ToCV was evaluated in experimental tomato fields sprayed alternately thrice a week with cyantraniliprole, acetamiprid, and flupyradifurone. Three areas were used: sprayed, no-sprayed, and control. The sprayed and no-sprayed areas consisted of 90% healthy tomato plants and 10% co-infected with ToSRV and ToCV, randomly interspersed. Adults of aviruliferous B. tabaci MEAM1 were released weekly in the sprayed and no-sprayed tomato plants. In the control area, only healthy tomatoes were placed. The experiment was repeated once. Symptoms were evaluated weekly and molecular tests were performed 70 days after transplanting to detect virus infection. The average rates of ToSRV and ToCV infection in the no-sprayed tomato plants in the first and second assays were 95% and 81%, respectively, while in the sprayed tomato plants, they were 6% and 7%. The control area did not show infected plants. Despite the relevant reduction, chemical control could not wholly prevent the secondary spread of the two viruses. Although the chemical management approach is highly efficient in killing B. tabaci MEAM1, insecticides have some limitations in their action, allowing variable rates of virus transmission. The demand for environmentally friendly control measures is growing, and new approaches are essential to reduce the volume and frequency of insecticide application to tomato crops while maintaining efficiency. The third objective was to evaluate the performance of the insecticide cyantraniliprole (CNAP) by developing a zein-based nanoinsecticide (ZeinCNAP). After 48 h of spraying, ZeinCNAP insect mortality dis not differ significantly from commercial CNAP. When the dose of ZeinCNAP was reduced to 1/10, insect mortality remained almost the same as commercial CNAP in full dose. The fresh mass weight, photosynthetic parameters, and oxidative stress of the tomato plants treated with ZeinCNAP were not affected compared to untreated plants. The developed nanoinsecticide has promising effects on B. tabaci MEAM1 mortality and can be considered safe for tomato plants. To our knowledge, this study is the first to evaluate the effects of zein nanoencapsulated cyantraniliprole on whitefly mortality.